The Evaluation of Electronic Based Government System using Statistical Product and Service Solutions (SPSS) - Kuncoro, Dony Yudy; Affandi, Achmad; Setijadi, Eko (Department of Electrical Engineering ITS and FORTEI, 2022)
SPBE is an information technology used by the government which is expected to improve government performance and meet people's expectations of government. This study uses primary data types by collecting data through online questionnaires using google form facilities. The results of this study found that the average quality of trust in SPBE services was 88.33 with a standard deviation of 12.25, so this indicates that the quality of trust in SPBE services, especially the Magetan Regency Government, is in good classification.